2015
DOI: 10.1515/cercles-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perceptions of deductive and inductive methods in teaching reading skills

Abstract: This article explores students' perceptions of inductive and deductive methods of teaching reading in Finnish and Hungarian in a higher education setting. A guided inductive discovery method of reading involves independent work and minimum vocabulary and grammar explanation before the reading assignment is given. A deductive pre-taught method involves grammar, vocabulary and content explanation before a text is read. Structured focus group interviews revealed that the advantages of the discovery method, i.e. g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In an argument concerning post-editing activities, Belam (2002) proposed that learners perform detailed analyses of source and target texts for improved understanding. Other recent studies (Jolley & Maimone, 2022;Valijärvi & Tarsoly, 2019) further concluded that using methods other than MT technology encourages output manipulation and negotiation of meaning. Another study by Lee (2020) provided evidence of the benefits of using MT in pedagogy.…”
Section: How Might Mt Affect Language Learning?mentioning
confidence: 97%
“…In an argument concerning post-editing activities, Belam (2002) proposed that learners perform detailed analyses of source and target texts for improved understanding. Other recent studies (Jolley & Maimone, 2022;Valijärvi & Tarsoly, 2019) further concluded that using methods other than MT technology encourages output manipulation and negotiation of meaning. Another study by Lee (2020) provided evidence of the benefits of using MT in pedagogy.…”
Section: How Might Mt Affect Language Learning?mentioning
confidence: 97%
“…In Larson-Guenette's (2013) study, most students responded that they use online writing tools daily because of time efficiency, word search, confirmation, and reference. And participants are using AI tools for writing despite being aware of its shortcomings (Valijärvi & Tarsoly, 2019…”
Section: Figure 1 Frequently Used Technology Toolsmentioning
confidence: 99%
“…And the convergence of AI and education has garnered significant attention with its numerous benefits for learners. Current digital-era learners are growing up with technology in daily life, and nearly all language learners use AI tools for learning language purposes, and most frequently use AI tools for L2 writing tasks (Valijärvi & Tarsoly, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We were able to show empirically that instructors have the knowledge and skills to accurately detect MT use most of the time, at least for now. This is good news, considering that access to technology and MT tools today is widespread among secondary and postsecondary L2 learners, who engage with MT tools frequently for academic purposes (Clifford et al, 2013; Enríquez Raído & Sánchez Torrón, 2020; Farzi, 2016; Fredholm, 2015; Jolley & Maimone, 2015; Larson‐Guenette, 2013; O'Neill, 2019; Sukkhwan, 2014; Valijärvi & Tarsoly, 2019).…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%